In-situ analysis of polymetallic nodules from the clarion-Clipperton zone, Pacific Ocean: implication for controlling on chemical composition variability - Li, Jie; Jin, Yinjia; Wang, Hao; Yang, Kehong; Zhu, Zhimin; Meng, Xingwei; Li, Xiaohu (Frontiers in Marine Science, 2024)
Polymetallic ferromanganese nodules (PMNs) in the Clarion-Clipperton Zone (CCZ) exhibit significant spatial variability in chemical composition, which complicates exploration efforts and increases associated costs. The primary factors driving this spatial variability remain unclear due to limited understanding of the growth history of these nodules. This study investigated the internal structure and elemental distributions of PMNs from both the eastern and western CCZ using a range of in-situ techniques, including high-resolution element mapping and chemical analysis, to characterize the compositional differences and growth processes of the nodules. Analysis of Nodule BC06 from the eastern CCZ reveals a decreasing Mn/Fe ratio from the inner part (Layer I) to the outer part (Layer II). In contrast, Nodule BC1901 from the western CCZ consists of three layers, with the Mn/Fe ratio increasing from Layer I to Layer II and then decreasing from Layer II to Layer III. Discrimination diagrams indicate that both nodules formed through hydrogenetic and diagenetic processes, with Nodule BC06 showing stronger diagenetic influences. Variations in diagenetic effects from core to rim suggest different geochemical controls in the two regions. In the eastern CCZ, compositional changes are mainly driven by the movement of PMNs away from the equatorial high-productivity zone. In the western CCZ, the variability in deep-water ventilation and the intensity of Antarctic Bottom Water are the key factors influencing nodule composition. These findings enhance our understanding of the growth history and spatial variability of PMNs in the CCZ and provide valuable insights for future resource evaluation.